Peran Bahasa Indonesia dalam Penyusunan Surat Dakwaan di Kejaksaan Tinggi Gorontalo - Duda, Verensyiah Sofyan Adam; Mooduto, Eko Purwanto; Dali, Meilina Widya; Fajar, Al; Mohama, Azizah Maharani; Hasni, Alwi; Sahrain, Abdi Praja; Taha, Rasya Abdillah; Dolongseda, Amelia; Machmud, Alfi Syahril Ramadhan; Montu, Adly Fairus; Adipu, Mohamad Alkindi Hernandya; Kaela, Brigita; Mokoagow, Sity Fauziah; Biludi, Hanifa Ramadhani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to analyze the role of standard Indonesian language usage in the drafting of indictments at the Gorontalo High Prosecutor’s Office, particularly in relation to clarity of meaning, structural accuracy, and the effectiveness of legal communication. The research employs a qualitative-descriptive method, with data collected through document analysis of selected indictments, interviews with prosecutors responsible for drafting the indictments, and observation of the indictment preparation process. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing to identify patterns of language use and their implications for the quality of legal documents. The findings indicate that the use of standard Indonesian plays a crucial role in ensuring legal certainty, preventing ambiguity, and strengthening juridical argumentation in indictments.